Analisis Efisiensi Biaya Operasi Bedah Umum Jaminan Kesehatan Nasional di Rumah Sakit Jakarta Tahun 2023 - Mahardhika, Jeffrey Christian; Soewondo, Prastuti; Permanasari, Vetty Yulianty; Pramanto, Heru (Journal Scientific of Mandalika (JSM) e-ISSN 2745-5955 | p-ISSN 2809-0543, 2025)
The National Health Insurance (JKN) program has increased the volume and revenue of inpatient general surgery procedures. However, Jakarta Hospital experienced a profit decline in 2023 due to low Indonesian Case-Based Group (INACBG) tariffs and cost inefficiencies. This study aims to analyze the cost efficiency of JKN-covered inpatient general surgeries as a basis for hospital development strategies. A descriptive-analytic method was applied, using activity-based costing to calculate procedure costs. Cost efficiency was assessed by comparing actual costs to normative benchmarks from clinical pathways, and further analyzed using Data Envelopment Analysis (DEA). Results indicate that unit costs were inefficient compared to normative standards (efficiency score: 101.9%, average: IDR 3,488,115.59), driven by high expenditures on medical services, drugs, and disposable medical supplies. Total costs, including accommodation, were also inefficient (score: 108.1%, average: IDR 4,729,373.69), with accommodation accounting for 26.2%. DEA identified perianal abscess incision as the most efficient procedure, while hemorrhoidectomy, inguinal herniotomy, and breast tumor excision were relatively efficient. Overall, inpatient general surgery procedures remain cost-inefficient. Enhancing efficiency requires stricter clinical pathway adherence, optimized use of drugs and supplies, reduced length of stay, and revised physician payment models. Promoting efficient procedures is essential for hospital sustainability.